2023
DOI: 10.1002/jobm.202200721
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory functions of oxylipins in fungi: A review

Abstract: Quorum sensing (QS) is a communication mechanism between microorganisms originally found in bacteria. In recent years, an important QS mechanism has been discovered in the field of fungi, namely, the lipoxygenase compound oxylipin of arachidonic acid acts as a QS molecule in life cycle control, particularly in the sexual and asexual development of fungi. However, the role of oxylipins in mediating eukaryotic communication has not been previously described. In this paper, we review the regulatory role of oxylip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…Previous research has shown that compounds like tyrosol and farnesol can boost the production of valuable secondary metabolites by affecting the secondary metabolism and modifying fungal morphology through gene regulation [ 24 ]. Many of these compounds function as QSMs, essential for microbial development and metabolic processes [ 20 , [25] , [26] , [27] , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that compounds like tyrosol and farnesol can boost the production of valuable secondary metabolites by affecting the secondary metabolism and modifying fungal morphology through gene regulation [ 24 ]. Many of these compounds function as QSMs, essential for microbial development and metabolic processes [ 20 , [25] , [26] , [27] , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
“…This influence extends to the regulation of genes involved in the synthesis of MK and MPs, underscoring the regulatory impact of oxylipins on Monascus biology. The research further explored the fungal quorum sensing regulation mechanisms, particularly focusing on the G protein-coupled signaling pathways, which are crucial for environmental sensing and response [ 25 ]. The role of oxylipins in mediating aflatoxin production in other fungi underscored the interconnectedness of QS, GPCRs, and G-protein-mediated signaling pathways, with this study reinforcing the impact of oxylipins on elevating cAMP levels and influencing MK synthesis gene transcription [ [41] , [42] , [43] ].…”
Section: Discussionmentioning
confidence: 99%